The Effect of Expressive Writing Therapy Combined with Self Efficacy on Quarter life crisis Score of Undergraduate Applied Nursing Program Students Poltekkes Kemenkes Tasikmalaya - Adhriani, Fefy; cahyati, peni; Riyana , Asep; Somantri , Iwan (Poltekkes Kemenkes Tasikmalaya, 2025)
Based on Riskesdas 2018, the prevalence of depression in Indonesia among individuals aged 15 and above reached 6.1%, with 2% originating from the Gen Z group (ages 15–24). This indicates the potential for psychological crises such as the Quarter life crisis (QLC). QLC commonly occurs between the ages of 18–30, especially among university students. Anxiety about the future, academic pressure, career uncertainty, and high social expectations contribute to the stress that leads to QLC. One intervention that can be provided is expressive writing therapy combined with self efficacy or self belief. This study aims to determine the effect of expressive writing therapy combined with self efficacy on QLC scores. The theoretical concepts underpinning this research include QLC, expressive writing therapy, and self efficacy. The method used is quantitative pre-experimental with a one-group pretest–posttest design involving 48 university students selected through simple random sampling. The intervention was conducted over four days within one week. Data were analyzed using a dependent t-test. The quarter life crisis instrument used in this study. The results showed a significant decrease in QLC scores from 4.4385 to 3.4427, with a reduction difference of 0.99583. The p-value was 0.000 (ρ < 0.05), indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This research demonstrates that expressive writing therapy combined with self-efficacy is effective in reducing Quarter life crisis scores among university students.